The Nuruls from a Linguistic Perspective as a Popular Youth Culture in Indonesia - Adam Muhammad Nur; Keni Pradianti (The Doctoral Studies Program of Linguistics of Udayana University, 2025)
In today's digital era, the expansion of language has been rapidly developing, allowing the representation of a word to shift or even for the meaning of that language to change. Moreover, in a language, the concepts of open and closed word classes are recognized, where open word classes are those that will continuously change and expand, while closed word classes are those that are unlikely to ever change or grow. Currently, among young people, the term